Equitable? Exploring ridesourcing waiting time and its determinants. (April 2021) - Yang, Hongtai; Liang, Yuan; Yang, Linchuan
Highlights: Waiting time (WT) is used as an indicator of equity of ridesouricng service. Trip, socioeconomic and built environment factors influence WT in Austin, TX. WT is positively related to traffic condition, surge multiplier, and rainy weather. WT is negatively related to road density, transit stop density, and land-use entropy. WT is higher in areas with high fraction of Hispanic/Latino and Black residents. Abstract: Waiting time (WT) is an important measure that can reflect accessibility to ridesourcing service. Previous studies explored the effects of built environment factors on WT based on estimated WT but did not control for trip-level characteristics, which may lead to biased parameter estimation. Thus, we further study this topic by using the actual WT recorded by the RideAustrin platform and considering trip-level variables. The single-level and multilevel proportional hazards models are constructed, and model comparison shows that the multilevel model performs better. We find that waiting time is positively correlated with trip-level characteristics such as traffic conditions, surge multiplier, and rainy weather. Regarding built environment factors, WT is positively related to distance to CBD and negatively related to road density, transit stop density, and land-use entropy. WT is also higher in areas with a high fraction of Hispanic/Latino and Black residents but lower in areas of low income.